A Joint Simon effect in children diagnosed with ASD is expressed differently from neurotypical children and adults. Issue 1 (7th February 2022) - Dudarev, Veronica; Iarocci, Grace; Enns, James T.
ABSTRACT: When two participants perform a go/no go task, sharing the same display but responding to different targets, their responses show a spatial compatibility effect. A shape on the side of a participant is responded to faster than that on the neighbour's side. This is called the Joint Simon effect (JSE), and it vanishes when participants perform the same task alone. JSE has been taken as evidence that humans automatically monitor the actions of others. Here we compare the JSE in adults, typically developing (TD) children, and children with autism spectrum disorder (ASD). Contrary to our expectations, we found a robust JSE in children with ASD. Ex-Gaussian analyses of the distributions of correct responses revealed that the JSE is later-acting in children with ASD. This implies more deliberate social processing, consistent with social camouflaging, which is a behavioural modulation undertaken by people with ASD in an attempt to conform to social norms. These findings support a social interpretation of the JSE while also revealing the unique nature of social processing in children with ASD.